Lauchlin Macleane and his connexion with East India Company politics 1773-1778 - Maclean, JNM (1964)
As every writer of a thesis or academic work is indebted in one way or another to many people for the sources and, quite frequently, the shape and inspiration for his dissertation, the manner of expressing his gratitude to those concerned has been rendered by custom, the limits of language and the restraints of British formality to a recognised formula. Indeed, the formula is so well recognised that it seems to defeat its purpose, and the gratitude expressed often appears to be no more than an imposed exercise in manners, dispassionate and infinitely cold, The present writer, although constrained to follow custom, must therefore insist that he records his thanks with both sincerity and humility, and that all the defects in this thesis are attributable to him alone. Above all others he is in the immeasurable debt of his Supervisor, Dr. Lucy Stuart Sutherland, C.B.E., The Principal of Lady Margaret Hall. But for her unfailing kindness, constant interest and painstaking guidance and criticism, this thesis would never have been started, let alone completed. Throughout its compilation Dr. Sutherland has always gone beyond the highest standards of supervision in order to throw light, either by discussion or written commentary, on innumerable matters concerned with the background or detail of the period. Móran taing a Dotair Liusaidh nic-Alasdair.